Gasto público como indicador de desempenho para as Instituições Federais de Ensino Superior - Simões, Lincon Rodrigues Dias (2011)
The present study investigated the appropriateness of using data about government’s expenditures in Federal Institutions of Higher Education (IFES) for evaluation of performance, starting up from the principle that Institutions which have better or equal results, consuming less inputs, have a good performance. The expenditures data were collected at the website Portal da Transparência do Governo Federal. Information about further inputs, which corresponded to the number of teachers and employees, were collected from Censo da Educação Superior do Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (INEP), as well as data about enrollment, considered as outcome measure. It was also considered post graduate’s enrollment in courses strictu sensu, collected at the application Geocapes. Also to represent the outputs or products, it was used the concept Índice Geral de Cursos (IGC) released by INEP. It was evidenced that there are universities which have used greater amounts of staff to produce the same results as their counterparts, but using lower amount of staff expenditures. Likewise, faced with institutions that have shown better performance, they have better or equal results, using proportionally few teachers and staff to serve their students, but which demonstrated a higher expenditures per student. There were evidenced also a weak correlation between IFES expenditures and outputs, expressed by the concept IGC, except as the costs with Financial Aid to Students, that were strongly correlated with the IGC. It was also evidenced situations where, even with reductions in others expenditures, an increase in total expenditures due to the representativeness of Staff Costs. So, considering the management staff expenditures is not under the control of local administrators, together with the representation they have spent, and the fact that the values spent are not reflected in equivalent amounts of inputs consumed, it is concluded that a systematic guided performance evaluation carried out by IFES in expenditures should not include staff’s expenses.